Rhein Exhibits Anti-Inflammatory Effects in Chronic Atrophic Gastritis via Nrf2 and MAPK Signaling - Song Liu,; Lei Shu,; Jiayao Yang,; Yi Liu,; Shu Zhang,; Nian Wang,; Zhaohong Shi, (Turkish Journal of Gastroenterology, 2023)
Background: Chronic atrophic gastritis is a premalignant lesion with a high risk of developing into gastric cancer. Rhein is a key active ingredient of several traditional Chinese medicines with multiple pharmacological effects. Nevertheless, the role of rhein in chronic atrophic gastritis is unclear.Methods: Helicobacter pylori infection was used to establish chronic atrophic gastritis in a mouse model. Murine gastric mucosa treated with saline or rhein was used in experiments. Hematoxylin and eosin staining and Alcian blue-periodic acid-Schiff staining were utilized for histopathological observation of murine gastric mucosa. The levels of proinflammatory factors were detected by enzyme-linked immunosorbent assay, and oxidative stress-associated markers were detected by commercially available assay kits. Western blotting was used for measuring the levels of nuclear factor, erythroid 2-like bZIP transcription factor 2, and mitogen-activated protein kinase signaling-related proteins.Results: Rhein mitigated the gastric mucosal injury and suppressed inflammation and oxidative stress in H. pylori-infected chronic atrophic gastritis mouse models. Rhein inactivated mitogen-activated protein kinase and activated erythroid 2-like bZIP transcription factor 2 signaling in gastric mucosa of mice with chronic atrophic gastritis.Conclusion: Rhein exhibits anti-inflammatory and antioxidant effects in chronic atrophic gastritis via erythroid 2-like bZIP transcription factor 2 and mitogen-activated protein kinase signaling.Cite this article as: Liu S, Shu L, Yang J, et al. Rhein exhibits anti-inflammatory effects in chronic atrophic gastritis via Nrf2 and MAPK signaling. Turk J Gastroenterol. 2023;34(5):525-532.